2009
DOI: 10.4038/cjsbs.v37i2.505
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation of Oyster Mushroom (<i>Pleurotus ostreatus</i>) on Sawdust

Abstract: A study was conducted to examine the effect of different types of spawns on oyster mushroom (Pleurotus ostreatus) production using sawdust. Locally available grains of kurakkan (Eleusine coracana), maize (broken) (Zea mays), sorghum (Sorghum bicolor), and paddy (Oryza sativa) were used for spawn production. Sawdust spawned with different types P. ostreatus spawns were examined for spawn running (mycelia development), pinhead formation and fruit body formation, mean yield, and biological efficiency. The experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 7 publications
3
31
2
Order By: Relevance
“…Spawn running was fastest in banana leaves substrates but the highest pileus diameter and stipe height were observed in mushroom from amended sawdust which took about four weeks for complete spawn running. Differences in rate of spawn running may be attributed to the size of the grains (Pathmashini et al, 2008).The suitability of amended sawdust agreed with the work of Shah et al (2004) who both advocated the effectiveness of sawdust in mushroom cultivation. Wheat straw substrate is one of the best substrates in Pleurotus ostreatus cultivation (Kumari and Achal, 2008) and the produce has average pileus diameter that is higher than the one obtained from amended sawdust.…”
Section: Effects Of Substrates On Minerals In P Pulmonarius and P Osupporting
confidence: 77%
“…Spawn running was fastest in banana leaves substrates but the highest pileus diameter and stipe height were observed in mushroom from amended sawdust which took about four weeks for complete spawn running. Differences in rate of spawn running may be attributed to the size of the grains (Pathmashini et al, 2008).The suitability of amended sawdust agreed with the work of Shah et al (2004) who both advocated the effectiveness of sawdust in mushroom cultivation. Wheat straw substrate is one of the best substrates in Pleurotus ostreatus cultivation (Kumari and Achal, 2008) and the produce has average pileus diameter that is higher than the one obtained from amended sawdust.…”
Section: Effects Of Substrates On Minerals In P Pulmonarius and P Osupporting
confidence: 77%
“…(3) Biological yield (g per bag), the whole cluster of fruiting bodies; economic yield (g per bag), cleaned fruiting bodies separated from cluster and dirty portion. (4) BE, biological efficiency: fresh weight of mushroom (g) per dry weight of substrate (g) × 100 (Pathmashini et al, 2008 contents, respectively (Ajonina et al, 2012). These authors observed differences in stalk length (2.43 to 3.24 cm) for P. ostreatus, whereas Monadal et al (2010) reported a decrease in the storage quality of the oyster mushroom with the increase of the pileus and stalk diameters.…”
Section: Resultsmentioning
confidence: 96%
“…Pathmashini et al (2008) recorded 276.87 g as the highest biological yield for strain PO2 in sawdust with kurakkan spawn.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Second, they are often focused on improving the availability of services to recepients instead of providing ownership. Third, they are run so as to guarantee the provision of services to all beneficiaries within a community (Pathmashini, Arulnandhy et al 2008). …”
Section: Agriculture and Paddy Farming Technologiesmentioning
confidence: 99%